2017
DOI: 10.1155/2017/1703810
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nrf2 in Ocular Diseases

Abstract: The human body harbors within it an intricate and delicate balance between oxidants and antioxidants. Any disruption in this checks-and-balances system can lead to harmful consequences in various organs and tissues, such as the eye. This review focuses on the effects of oxidative stress and the role of a particular antioxidant system—the Keap1-Nrf2-ARE pathway—on ocular diseases, specifically age-related macular degeneration, cataracts, diabetic retinopathy, and glaucoma. Together, they are the major causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 179 publications
(254 reference statements)
0
59
0
Order By: Relevance
“…Previous studies have demonstrated that impairment of the NFR2 pathway plays a key contributing role in the pathogenesis of diabetic retinopathy (as reviewed in refs. 41 and 42 ). Further studies should be conducted to analyze GHRH-R-mediated activation of the NRF2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that impairment of the NFR2 pathway plays a key contributing role in the pathogenesis of diabetic retinopathy (as reviewed in refs. 41 and 42 ). Further studies should be conducted to analyze GHRH-R-mediated activation of the NRF2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As oxidative stress due to cigarette smoke, 66 exposure to sunlight, 67 and other environmental factors is likely contributing to AMD development, it may be of significance that the NRF2 pathway that regulates a protective antioxidant response 68 was found enriched in nAMD and PDR by GSEA analysis ( Table 2). Oxidative stress may also be important for dry AMD 69 because GPX3, SOD1, SOD3, and CAT involved in the regulation of reactive oxygen species and part of the oxidative stress pathway were upregulated ( Table 2; Supplementary Table S2), even though enrichment was weak (FDR: 0.261).…”
Section: Discussionmentioning
confidence: 99%
“…The complete clinical data were collected for each subject. Patients with the following diseases were excluded: Other malignant tumors, acute infection, cardiovascular diseases, chronic obstructive pulmonary disease, neurodegenerative diseases, liver diseases and ocular diseases, including age-associated macular degeneration, cataracts, diabetic retinopathy and glaucoma ( 5 , 7 9 , 11 13 ). The present study was approved by the Ethics Committee of Gansu Provincial Hospital and all patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%